Salary survey methods: Comparability problems - R. J. Snelgar (South African Journal of Business Management, 1986)
Most organizations regard the accurate determination of prevailing labour market rates as being of primary importance to decisions regarding the setting of competitive wage and salary levels. The techniques involved in establishing these rates are fraught with problems, mainly revolving around efforts at obtaining comparability. Justification has been provided for organizations using tailor-made survey approaches in preference to professional or 'commercial' surveys, as this allows reduction to a minimum of such comparability problems as those associated with job description responsibilities, and compensation mix. This study reveals the extent to which a single pay structure received differing adjustments as a result of analysis of data obtained from a tailor-made survey approach as opposed to that obtained from a 'commercial' survey. Results indicate significant differences in adjustments over a three-year survey period, attributable essentially to the wide range of comparability difficulties associated with use of 'commercial' survey data.
Keywords: 650